P Pengaruh Penambahan Puree Labu Siam (Sechium edule) Terhadap Sifat Fisikokimia dan Sensori Otak-Otak Ikan Kuniran (Upeneus sulphureus) - Hanifah Septiana Putri; Dyah Koesoemawardani; Esa Ghanim Fadhallah; Sri Hidayati (Jurnal Agroindustri Berkelanjutan, 2025)
Otak-otak in general are processed products with low fiber content, so the use of chayote puree can increase fiber content and improve the texture of otak-otak. This study aims to determine the effect of the addition of chayote puree on the physicochemical and sensory properties of kuniran fish otak-otak and the best concentration of chayote puree addition on the physicochemical and sensory properties of kuniran fish otak-otak according to SNI 7757:2013. This study used a Randomized Complete Group Design (RAKL) with a single factor and four replicates. This research uses the formulation of adding chayote puree with 6 levels, namely P1 (0%), P2 (5%), P3 (10%), P4 (15%), P5 (20%), and P6 (25%). The data obtained were analyzed for homogeneity with Bartlett's test and data multiplicity was tested with Tuckey's test, then the data were analyzed for variance to determine the effect of treatment. If there is a significant effect, the data is further analyzed with the Honest Real Difference Test (BNJ) at the 5% level. The best otak-otak results are treatment P6 with the addition of chayote puree as much as 25% with the criteria of water content 52.99%, hardness 445.94 gf, cohesiveness 0.87, springiness 10.30 mm, L 73.68, a* 4.15, b* 9.73, color 2.75 (not brownish yellow), texture 4.58 (chewy), aroma 3.92 (somewhat typical of fish), taste 4.11 (like), and overall acceptance 4.11 (like). Kuniran fish otak-otak with the addition of chayote puree can increase fiber by 1.58% of the daily requirement.